Forgetting Something Part 2: Reducing Emergency Department (ED) Revisits While Increasing Patient Experience With An ED Automated Pharmacy Kiosk - Austin Garver; Janeliz Mercado Santana; Jacqueline Espinoza Ramirez; Oscar Santalo (Journal of Acute Care Pharmacotherapy, 2026)
Introduction Emergency department (ED) revisits defined as return visits within 72 hours or 30 days serve as key indicators of patient-care quality, with medication non-adherence being a major contributor [2]. “Meds-to-beds” programs and automated pharmacy systems have emerged as strategies to address persistent challenges in ensuring timely and safe medication access at hospital discharge. Prior studies have demonstrated that these interventions reduce prescription abandonment and improve the quality and continuity of care. As patient satisfaction plays a growing role in medication adherence and overall outcomes, the addition of automated medication kiosks to the ED discharge process may improve both quality of care and the patient experience in a fast-paced clinical setting. Objectives To determine whether an ED medication kiosk onsite reduces ED revisits and increases patient satisfaction. Methods A retrospective quality-improvement analysis was conducted at an off-site emergency department (OSED) and parent-campus emergency department (CED) from July 15th to August 12th, 2025. Primary outcomes for the ED revisit arm was all-cause revisit in 72-hours or 30-days and 30-day revisit in relation to primary diagnosis. For patient satisfaction, a survey was conducted to assess convenience and satisfaction. The secondary outcome was a 30-day ED revisit cost avoidance analysis. Results Among 309 evaluated patients, 154 used the kiosk, and kiosk utilization was associated with reduced ED revisits, including a 1.9% decrease (p-value 0.57) in 72-hour revisits and a 3.2% decrease (p-value 0.53) in 30-day revisits. At the health-system level, this 30-day reduction translates to an estimated $2.5 million in ED revisit cost avoidance annually. Of the 132 patients contacted, 43 completed the satisfaction survey (32% response rate), and rated the bedside medication delivery as “extremely convenient and an extremely positive experience.” Conclusion The implementation of medication kiosks reduced both 72-hour and 30-day revisits, provided a positive patient experience, and showed a possible health-system cost avoidance of ED revisit prevention by over $2 million dollars.